Solvent Extraction Studies on Copper(II) and Silver(I) Complexes of Bis(4-hydroxypent-2-ylidene)diaminoethane: Composition of Extracted Copper(II) Species - P. O. Ukoha; F. I. Nwabue; L. N. Obasi (E-Journal of Chemistry)
Copper(II) complexes of bis(4-hydroxypent-2-ylidene)diaminoethane (BHPDE) were prepared by extractive method. Job’s continuous variation and equilibrium constant methods, as well as spectral and elemental analyses were applied in the determination of the nature of extracted species. The results indicate the formation of mixed ionic complexes of the types Cu(H2L)X2, Cu(H2L)2X2 and CuL (where H2L = BHPDE and X = NO3-, CIO4-, Cl- or ½SO42-). Cu(H2L)X2 and Cu(H2L)2X2 predominate at low pH extractions while CuL chelate predominates at high pH extraction. The complexes exist in two isomeric forms, the blue readily-water-soluble and the violet less water-soluble forms. Both complexes show maximum absorption at 540 nm and molar absorptivity values of about 2.0 x 102 dm3 mole-1 cm-1.